Linear vs. Log-linear Unit-Root Specification: An Application of Mis-specification Encompassing. - Spanos, A; Hendry, D; Reade, J (Blackwell Publishing, 2008)
The objective of this paper is to apply the mis-specification (M-S) encompassing perspective to the problem of choosing between linear and log--linear unit-root models. A simple M-S encompassing test, based on an auxiliary regression stemming from the conditional second moment, is proposed and its empirical size and power are investigated using Monte Carlo simulations. It is shown that by focusing on the conditional process the sampling distributions of the relevant statistics are well behaved under both the null and alternative hypotheses. The proposed M-S encompassing test is illustrated using US total disposable income quarterly data.